Fun Speaking with Cue Card - Ahmad Mursyid; Fitrotul Mufaridah (ELLITE, 2019)
English has become crucial to be acquired by the second or foreign language (ESL/EFL) learners  to assist them with their academic life. In addition, it is essential for one to be able to speak in English. However, it is not easy for second or foreign language (ESL/EFL) learners to acquire good speaking skills. EFL learners in Asia; not to mention in Thailand are also facing similar problem.  This study is aimed to how the use of cue cards as media to teach English can improve the EFL learners in Thailand.  The study was conducted in one of junior high schools in Thailand.  Classroom Action Research (CAR) was employed in this study. Observation and test were applied to collect the data. The result of the study revealed that this media is able to improve the speaking ability of the learners.